2008
DOI: 10.1111/j.1365-2788.2008.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Working memory functioning in children with learning disabilities: does intelligence make a difference?

Abstract: These findings do not support the notion of different cognitive functioning because of differences in intelligence of these two groups. In the ongoing discussion about the role of intelligence (especially as to the postulated discrepancy between intelligence and school achievement in diagnosis and special education), our findings might lead to rethinking the current practice of treating these two groups as fundamentally different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 25 publications
11
53
0
6
Order By: Relevance
“…Furthermore, Maehler and Schuchardt (2009) suggest that children with dyslexia and a low IQ present the same working memory impairment as those with an average or above average IQ, reinforcing that differences based on the level of intelligence, observed between groups in this study, may not interfere signifi cantly with the performance of other cognitive functions and the differences actually obtained occur due to LD.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, Maehler and Schuchardt (2009) suggest that children with dyslexia and a low IQ present the same working memory impairment as those with an average or above average IQ, reinforcing that differences based on the level of intelligence, observed between groups in this study, may not interfere signifi cantly with the performance of other cognitive functions and the differences actually obtained occur due to LD.…”
Section: Discussionsupporting
confidence: 79%
“…Their study further demonstrated that dyslexic children with a low IQ presented the same working memory impairment seen in those with an average or above average IQ, reinforcing the importance of discussing the level of intelligence --measured through the Wechsler Intelligence Scale for Children (WISC) -among children with LDs (Maehler & Schuchardt, 2009). Accordingly, Kibby (1999, cited by Kibby & Cohen, 2008 shows that verbal working memory, phonological awareness and verbal intelligence (VIQ) are involved in the decoding of pseudowords and that such abilities can affect language.…”
Section: Neuropsychological Characteristics Of Dyslexiamentioning
confidence: 89%
“…Furthermore, Arffa (2007) found correlations between full scale IQ and EF measures of planning, fluency and inhibition, but not trail-making (often described as assessing switching). Mähler et al (2009) investigated the distinction between learning and intelligence by including two groups with learning difficulties in their study, one with Executive Functioning in Intellectual Disability 4 typical IQ scores (together with a specific learning difficulty), and one with generally low IQ scores. No differences were found between the two groups on EF measures, but both groups performed more poorly than a comparison group with typical IQ and no learning problems.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies of children with ID have included measures of ELWM, generally reporting MA appropriate performance for children with ID (e.g. Brown, 1974;Connors et al, 1998;Henry & MacLean, 2002;Henry & Winfield, 2010;Mähler et al, 2009). Yet some inconsistency in the literature is also apparent: a few authors have reported that children with ID perform more poorly than MA comparisons (Russell et al, 1996;van der Molen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Arffa (2007) also found that IQ was related to EFs tests of sorting, fluency and inhibition, but not to trail-making. Maehler and Schuchardt (2009) made a distinction between learning and intelligence by including both a group with learning difficulty and normal IQ and a group with learning difficulty and low IQ. No differences were found between the two groups on EF measures, but both performed more poorly than a control group without Executive Functions in Intellectual Disability 4 learning problems and normal IQ.…”
Section: Introductionmentioning
confidence: 99%